Complete mitochondrial genome of Mustela sibirica (Carnivora: Mustelidae), a protected and endangered species in China - Gao, Wei (Mitochondrial DNA B Resour, 2020)
We sequenced the complete mitochondrial genome (mitogenome) of Mustela sibirica in China by the shotgun genome skimming methods. The mitogenome of M. sibirica is 16,558bp in length with the base composition of 32.9% A, 27.3% T, 26.0% C, and 13.9% G, and consists of 13 protein-coding genes (PCGs), 22 tRNAs, two rRNAs, and one non-coding control region. The 13 PCGs use ATG as initiation codons except ND3, ND5 and ND2 which initiate with codons ATA and ATT, respectively. Four (COX3, ND1, ND2 and ND4) of the 13 PCGs terminate with a single T– –, and the remainder with a TAA termination codon except ND3 and CYT B using TA– and AGA as termination codon. The phylogenetic tree based on 13 protein-coding genes indicated that M. sibirica is sister to the clade grouped with three species M. nigripes, M. eversmannii, and M. putorius, and Mustelinae species formed a monophyletic group, which is close to the Lutrinae clade within Mustelidae.